Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

triangles

Asked by 13th February 2009, 10:14 PM
Answered by Expert
Answer:

Pls check the To Prove statement. It should be BD2-CD2=2CD.AD

Consider L.H.S

BD2-CD2

= AB2-AD2-CD2 (By pythagoras theorem in triangle ABD)

= AC2-AD2-CD2 (As ABC is isosceles triangle where AB=AC)

=(AC+AD)(AC-AD)-CD2

=CD(AC+AD)-CD2

=CD(AC+AD-CD)

=CD.2AD = 2AD.CD

Answered by Expert 5th March 2009, 12:40 PM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!